2020
DOI: 10.1017/s109285292000173x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vortioxetine in subjects with major depressive and alcohol use disorders: a 6-month retrospective analysis

Abstract: Background Major depressive disorder (MDD) and alcohol use disorder (AUD) are highly comorbid, with greater clinical complexity and psychosocial impairment. Several antidepressants have been used in this population, with mixed results. This preliminary study aims to investigate the effects of the multimodal antidepressant vortioxetine in MDD + AUD subjects. Methods We retrospectively evaluated 57 MDD + AUD and 56 MDD outpatients, matched for baseline characteristics. Patients were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 80 publications
2
14
0
Order By: Relevance
“…Improvements in general functionality, quality of life, and anxiety have also been reported with vortioxetine (14). The data of vortioxetine use in cases of comorbid AUD and MDD are limited, but the results also appear to be promising (83).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Improvements in general functionality, quality of life, and anxiety have also been reported with vortioxetine (14). The data of vortioxetine use in cases of comorbid AUD and MDD are limited, but the results also appear to be promising (83).…”
Section: Resultsmentioning
confidence: 97%
“…Despite the high prevalence of alcohol use disorder (AUD) and MDD comorbidity, and the severity and adverse consequences of both diseases, the available evidence is still inadequate to even outline the treatment strategies for these patients, and the treatment guidelines have failed to reach consensus on the issue (83). Systematic reviews have reported that SSRIs, SNRIs, and TSAs show some efficacy in improving both depressive symptoms and some AUD-related traits, including the number of drinks per drinking days and the number of patients who abstained from alcohol use (84)(85)(86).…”
Section: -Effect Of Vortioxetine With Comorbid Alcohol Use Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…As AUD is often comorbid with different neuropsychiatric disorders, antidepressants and antipsychotics are often potential alternatives. For example, recently given its effectiveness on mood, cognition, and functioning; its good safety and tolerability profile; and its low potential for abuse, vortioxetine could represent a valid pharmacological intervention in AUD-comorbid MDD patients as part of an integrated therapeutic rehabilitation program ( 49 ).…”
Section: Discussionmentioning
confidence: 99%